IRRIGATION EFFICIENCY AND UNIFORMITY OF AEROPONICS SYSTEM - Prastowo Prastowo; S. Hardjoamidjojo; N. Laelasari (Jurnal Keteknikan Pertanian, 2007)
ABSTRACT The evaluation of the irrigation efficiency and coefficient of unttotmity (CU) of the existing aeroponics system has been conducted for one growing season of petsai (Brassica pekinensis L) in Parung - Bogor, Indonesia. The evaluation covers the CU of the spray discharge, pH, temperature and electrical conductivity (EC) of the nutrient solution. It was concluded that the CU of spray discharge, pH and temperature of the nutrient solution were relatively high, but the CU of EC of the nutrient solution was relatively low. Conveyance efficiency and water-use efficiency were about 84.38% and 40.09%, respectively. The average crop water requirement was about 1,457 cc/crop/season or equal to 16,870 cc per Kg of petsai produced. Diterima: 02 Januari 2007, Disetujui: 19 Pebruari 2007